2010
DOI: 10.1017/cbo9780511762888
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Political Science and the Study of Causality

Abstract: Increasingly, political scientists use the term 'experiment' or 'experimental' to describe their empirical research. One of the primary reasons for doing so is the advantage of experiments in establishing causal inferences. In this book, Rebecca B. Morton and Kenneth C. Williams discuss in detail how experiments and experimental reasoning with observational data can help researchers determine causality. They explore how control and random assignment mechanisms work, examining both the Rubin causal model and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(123 citation statements)
references
References 0 publications
3
109
0
5
Order By: Relevance
“…To the extent that they are homogeneous, student subject pools lack variation on key individuallevel covariates that might condition reactions to experimental stimuli (Krupnikov and Levine 2013). Although representative samples are required for experimental research, random assignment of participants to treatment and control conditions ensures observed treatment effects are caused by the experimental manipulation rather than unobserved, systematic differences among participants (Druckman et al 2011;Kinder and Palfrey 1993;Morton and Williams 2010). Nonetheless, diversity adds value by allowing researchers to explore and verify factors that moderate treatment effects.…”
Section: Diversity and Heterogeneous Treatment Effectsmentioning
confidence: 99%
“…To the extent that they are homogeneous, student subject pools lack variation on key individuallevel covariates that might condition reactions to experimental stimuli (Krupnikov and Levine 2013). Although representative samples are required for experimental research, random assignment of participants to treatment and control conditions ensures observed treatment effects are caused by the experimental manipulation rather than unobserved, systematic differences among participants (Druckman et al 2011;Kinder and Palfrey 1993;Morton and Williams 2010). Nonetheless, diversity adds value by allowing researchers to explore and verify factors that moderate treatment effects.…”
Section: Diversity and Heterogeneous Treatment Effectsmentioning
confidence: 99%
“…There is a plethora of publications in the political science literature about specific aspects of research design and methodologies applied in the field such as interviews (Arksey andKnight 1999, Mosley 2013), experiments (Druckman et al 2011, Morton andWilliams 2010), or focus groups (Stewart et al 2006). Yet, these publications often ignore specific organisational issues to be addressed by political scientists before entering the field, or only mention them as a side-note.…”
Section: Literature Overview: Neglecting Organisational As-pectsmentioning
confidence: 99%
“…Vienu atveju validumas suprantamas kaip metodo objektyvumas, kitu -kaip patikimumas ir kt. Todėl autorius siūlo laikytis tokios šios sąvokos traktuotės: metodo validumastai jo tinkamumas, kitaip tariant, jis užtikrina, kad atliekant tyrimą nėra sisteminės paklaidos, matuojama būtent tai, ką norima matuoti (Kardelis, 2002 Apibendrinant metodologinėje literatūroje (Kardelis, 2002;Stonkus, 2002;Morton, Williams, 2010;Hooghe, 2010;Druckman, Kam, 2011;Kittel, Morton, 2012, kt. ) pateikiamas nuomones, galima teigti, kad vidinis validumas rodo priklausomojo kintamojo pokyčius, kurie buvo nulemti jo sąveikos su nepriklausomuoju kintamuoju.…”
Section: Eksperimentinių Tyrimų Kokybės Reikalavimaiunclassified
“…Laboratoriniuose eksperimentuose yra didžiausia eksperimento sąlygų, elgsenos skatinimo ir elgesio sąlygų kontrolė, tad tokių tyrimų konstrukcinis patikimumas ir priežastingumo patikimumas -pagrindiniai vidinio patikimumo aspektai -yra dideli (Morton, Williams, 2010). Tačiau statistinis laboratorinių eksperimentų patikimumas socialinių mokslų tyrimuose dažnai gali būti menkas.…”
Section: Eksperimentinių Tyrimų Kokybės Reikalavimaiunclassified